Clean water projection of Serang City, Banten Province - Restu Wigati; Woelandari Fathonah; Hendrian Budi Bagus Kuncoro; Heri Mulyono (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
Indonesia is predicted to experience a deficit in groundwater availability in 2040, covering urban areas, including Serang City. The increasing urban population has become a new burden on the water supply, which has been relying on groundwater. Pandemic Covid-19 adds new challenges while simultaneously realizing the need for aspects of clean and healthy living behavior to minimize the potential for spreading the virus. Based on these conditions, it is necessary to conduct a study related to the projection of the need and availability of clean water in Serang City until 2031, as well as efforts to anticipate the fulfillment of clean water, and solutions to problems, especially in urban areas through sustainable development related to the need for clean water that is environmentally friendly and has a concept of environmental sustainability. Based on the analysis results, it is obtained that the projected clean water needs of Serang City for domestic and non-domestic clean water needs and the need for clean water that can be treated are insufficient. The clean water production capacity of PDAM Tirta Albantani and PDAB Tirta Madani, a supplier of clean water in Serang City, is not yet optimal, so it needs new technology; the concept of the City cares about clean water using nature-based technology.